Cost-Effectiveness Analysis of Favipiravir and Remdesivir as COVID-19 Treatment in South Tangerang, Banten Province - Indonesia - Putro, Wahyu G.; Fahriyati, Andriani R.; Julian, Gilberto A.; Amalia, Tania R.; Riski, Zaki M. (Pharmacology and Clinical Pharmacy Research, 2023)
COVID-19 is a contagious ailment primarily attributed to the severe acute respiratory syndrome coronavirus. Indonesia persists in confronting the COVID-19 pandemic, and South Tangerang City has emerged as one of the municipalities in Indonesia that has been significantly affected. There are two categories of medications employed for COVID-19 treatment according to government policies, namely favipiravir and remdesivir. This study aims to as- sess the cost-effectiveness of favipiravir and remdesivir medications at the South Tangerang General Hospital, Indonesia. The present study employs a retrospective research design characterized by a quantitative approach, utilizing cross-sectional methodologies. The analy- sis mostly consists of descriptive techniques. The sample consisted of 479 individuals, with 246 individuals receiving outpatient treatment and 233 undergoing inpatient treatment. The inclusion criteria for this study consisted of individuals diagnosed with COVID-19 who had tested positive for the antiviral medications favipiravir and remdesivir. The findings indicated that the Average Cost-Effectivenss Ratio (ACER) for inpatients treated with fa- vipiravir was IDR 2,354,319,859, but for those treated with remdesivir, it amounted to IDR 3,501,513,488. Regarding the outpatient population utilizing favipiravir, the total expendi- ture amounts to IDR 420,083,118. Similarly, patients utilizing remdesivir incur a total ex- penditure of IDR 797,282,432. It is worth noting that the Cost-Effectivenss Ratio (CER) for patients using favipiravir is IDR 1,545,621, whereas patients using remdesivir have a CER of IDR 2,309,705. This study makes a valuable contribution to the existing body of research by demonstrating the cost-effectiveness of favipiravir. Consequently, future studies inves- tigating the overall effectiveness of favipiravir in COVID-19 patients must employ more comprehensive criteria.